The Material Insight Between Buddhism and Marxism - Farha, Mohammad (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Could Buddhism really comptete Marxism in its material tendency? This would be the point of focus of this piece of research through a comparative study between Buddhism and Marxism in the light of the viewpoint of each of them toward materialism and such relevant issues as the cosmos, God, religion, consciousness, dialectics….etc. therefore, we shall endeavor basically to prove that Buddhism was not—- as is believed —- a philosophical spiritual school, quite contrastively, it was a realistically dynamic materialistic school. If we could strike this point, Buddhism would be in the same domain as Marxism. This is so if we did not consider them two cumulative school. Needless to say that a few discrepancies whether relating to methodological or to the change of the spacio- temporal or social change have been closely scrutinized.